1992
DOI: 10.4315/0362-028x-55.10.763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment Conditions on Nisin Inactivation of Gram-negative Bacteria

Abstract: A method using nisin and a chelating agent to inactivate Salmonella species and other gram-negative bacteria has been developed. The objective of this study was to determine the effect of treatment conditions on the application of this method. Ten gram-negative organisms were used in this study, including six Salmonella species commonly associated with foodborne illness. Organisms were selected on the basis of sensitivity to nisin and a chelating agent. The following parameters were examined: (a) chelating age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 0 publications
3
55
0
2
Order By: Relevance
“…8) Nisin is active against a wide range of gram-positive bacteria, although it is not effective against gramnegative bacteria. 9) However, when used in combination with agents destabilizing the outer membrane, it can inhibit gram-negative bacteria. -Cymene (4-isopropyltoluene or 1-isopropyl-4-methylbenzene) is a biological compound naturally present in the essential oils of oregano and thyme.…”
mentioning
confidence: 99%
“…8) Nisin is active against a wide range of gram-positive bacteria, although it is not effective against gramnegative bacteria. 9) However, when used in combination with agents destabilizing the outer membrane, it can inhibit gram-negative bacteria. -Cymene (4-isopropyltoluene or 1-isopropyl-4-methylbenzene) is a biological compound naturally present in the essential oils of oregano and thyme.…”
mentioning
confidence: 99%
“…Other authors have noted the role of bacteriocins from Lactobacillus plantarum BN in improving the shelf-life of the refrigerated bovine meat (Fiorentini et al, 2001) and effectiveness of the concomitant application nisin/EDTA in inhibiting the growth of Gram-negative bacteria (Salmonella tiphymurium. S. infantis, S. heidelberg, S. choleraesuis, E. coli O157:H7) (Stevens et al, 1992;Cutter and Siragusa, 1995). Shefet et al (1995) found inhibitory effect of nisin when applied in combination of ETDA and citric acid on S. typhimurium in chicken meat.…”
Section: Resultsmentioning
confidence: 99%
“…The refrigerated pizza doughs are recognized as excellent substrates for the microbial growth being necessary to apply some procedures in order to control the growth and microbial survival in/on them (Cabo et al, 2001). Several authors have reported high microbial contamination in the food doughs (Stevens et al, 1992;Freitas et al, 2004). Staphylococcus has been known as pathogen microorganisms able to survive in the refrigerated pizza doughs (Freitas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The nisin stock solution was prepared by dissolving 0.1 g of nisin in 10 mL of 0.02 N HCl (17). This solution was used to prepare the required nisin concentrations.…”
Section: Chemicalsmentioning
confidence: 99%
“…but does not inhibit the majority of Gram-negative bacteria (1,6,11). Nisin showed to be efficient in inactivating Gram-negative bacteria when used together with chelating agents (EDTA), causing an aberration in cell membrane lipopolisaccharyde component (17).…”
Section: Introductionmentioning
confidence: 99%